Surfaces Casting Defect Analysis and its Countermeasures on Products Manufactured by Alkali-Phenolic Binder Sand Molding - Aditianto Ramelan; Ekavianty Prajatelistia; Susana Susana; Muhammad Fathurrohman; Husen Taufiq (Jurnal Metal Indonesia, 2022)
This paper presents the results of the analysis of surface casting defects and their countermeasures. To find out the root causes of defects, and their mechanisms. Product casting defects have been characterized by visual inspection and SEM/EDX, also collecting production data information. Studied relation between the composition of molding sand and the mechanical properties of compressive strength and surface stability index has been done. The visual inspection results, field data collection, and SEM/EDX analysis showed a rough product surface and the presence of SiO2 inclusions. The product has been made with an alkaline phenolic mold using reclaimed sand with a compressive strength of 18 kg/cm2. The study results show that with increasing binder levels, there is an increase in the mechanical properties of compressive strength and surface stability index. They were based on the experimental results of the test block product casting with improved mechanical properties above. Obtained a much better surface of the casting product, and relatively no surface inclusion defects were found. The above experiment shows that the surface stability index is an important parameter the critical value is 90%, and the necessary compressive strength is 20 kg/cm2. The effect of Loss on Ignition content on mechanical properties is also reviewed.